2013
DOI: 10.1016/j.ijimpeng.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment on the ballistic properties of AA6070 aluminium alloy

Abstract: The ballistic properties of the aluminium alloy AA6070 in different tempers are studied, using target plates of 20 mm thickness in tempers O (annealed), T4 (naturally aged), T6 (peak strength) and T7 (overaged). The stressstrain behaviour of the different tempers was characterised by quasi-static tension tests and was found to vary considerably with temper in regards to strength, strain hardening and ductility. Ballistic impact tests using 7.62 mm APM2 bullets were then carried out, and the ballistic limit vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 30 publications
6
46
0
Order By: Relevance
“…The results obtained by this approach are validated against an experimental study reported in Holmen et al [17] on the perforation of 20 mm AA6070 plates by 7.62 mm AP…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…The results obtained by this approach are validated against an experimental study reported in Holmen et al [17] on the perforation of 20 mm AA6070 plates by 7.62 mm AP…”
Section: Introductionsupporting
confidence: 56%
“…The plates were heat treated to tempers O (annealed), T4 (naturally aged), T6 (peak strength) and T7 (overaged) according to Table 2. The material was characterised by quasi-static tensile tests in different in-plane directions at ambient temperature to determine the yield strength, work hardening, tensile strain to failure and plastic anisotropy, see [17] for details. It was found that the anisotropy in strength and work hardening was negligible, while the tensile strain to failure varied considerably with direction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, again in contrast to the results shown in Fig. 11 and Table 4, it is of interest to note that significantly changing the mechanical properties of an aluminium alloy, via a heat treatment, is known to affect the ballistic performance of both thin [36] and thick [37,38] monolithic aluminium alloy sheets. However, from the results shown in Fig.…”
Section: Perforation Of the Fml Panels During The High-velocity Impacmentioning
confidence: 80%